Climate evolution across the earth's history - Sánchez Santillán, Norma (2014)
In a natural way, the atmosphere –and therefore the climate- evolved together with the continent, the ocean, the interior Earth an all the other planetary components. This co-evolution was often via catastrophes, certainly very fruitful, especially for the biological evolution and diversification. In several stages, the volcanism contributed ingredients to the atmosphere, as much more arrived with the comets and meteorites; the ocean brought water vapor to it with its successive state changes; the continental drift increased the oceanity and decreased the continentality of climates. The ocean gave also thermal inertia and so stability to the climate. The oxygen appearance favored the life, and its subsequent photochemical dissociation and recombination yielded the stratospheric ozone layer. The spontaneous fires put upper limit to the atmospheric concentration of the oxygen generated by the vegetation, making up the present atmosphere.